Validasi Metode Pengujian Amonia Menggunakan Metode Uji Cepat Hanna HI 96733 - Siti Nuraini; Hanida Yanti (Jurnal Penelitian Sains, 2020)
Validation of ammonia testing methods using the Hanna HI 96733 rapid test method has been performed. Hanna HI 96733 rapid test method has advantages that cost more economical because using only 2 reagents and more practical, the number of sample volume used relatively little so that the waste produced is also less, the analysis is easier and faster. The validation parameters that are performed are test linearity, Method Detection Level (MDL), precision test and accuracy test, so that the method can be known is valid or not. Ammonia testing with HI 96733 has linearity (r) 0.9993 for concentration range 5 – 50 ppm, MDL of 0.4752 ppm, precision of 5.2505% and accuracy of 100.48%. The rapid test method of Hanna HI 96733 can be used as a method of testing ammonia in LPT FMIPA because it meets all the acceptance limits.